STUDI PENGEMBANGAN MODEL HIDROGRAF SATUAN SISTETIS SNYDER UNTUK SUNGAI –SUNGAI DI SULAWESI SELATAN - MUHAMAD YAMIN (Universitas Mahasaraswati Mataram, 2019)
This study aims to analyze the parameters that influence the Snyder synthetic unit hydrograph method. The study was conducted on 11 watersheds in South Sulawesi Province, 8 watersheds for modeling and 3 other watersheds for reliability testing (model verification). With rainfall data, the discharge data and watershed characteristics obtained from each watershed were analyzed for parameters that affected the hydrograph breakdown of the Snyder HSS method. Then compared to the hydrograph of the observation unit which was analyzed by the Collins method. After calibration was done with the NASH criteria obtained Peak Time (Tp) = 97.996%; Peak Discharge (Qp) = 98.331% and Basic Time (Tb) = 99.700%. The curved delineation of the hydrograph uses the auxiliary point W, which gives the result of volume deviation, namely: 7.980%, 9.227%; 6.855%; 4.966%; 10.972% and 9.843% are relatively small when compared to the model using Alexejeyev Arch with deviations: 22.362%; 29.991%; 26,319%; 19.602%; 29,786% and 17,633%.